Modern cryptanalysis of the Truppenschlüssel. Issue 3 (4th May 2023) - Ostwald, Olaf; Weierud, Frode
Abstract: Truppenschlüssel (troop cipher) was a manual cipher used by the German Army during World War II. Based on more than a hundred authentic messages that survived the war, a cryptanalysis is performed. The exact encryption procedure is investigated via two plaintext-ciphertext compromises. A specific ciphertext-only breaking tool is developed, utilizing the hill climbing technique. This leads to successful breaks of most of the messages.